Single tin-vacancy center in nanoscale diamond - Masanori Fujiwara; Masanao Ohori; Frederick Tze Kit So; Yuto Makino; Naoya Morioka; Izuru Ohki; Ryuji Igarashi; Masahiro Nishikawa; Norikazu Mizuochi (Discover Nano)
Abstract Group-IV color centers in diamonds are promising not only as spin–photon interfaces for quantum networks but also as multicolor photoluminescence probes and all-optical temperature sensors for biological research. Therefore, generating group-IV color centers in detonation nanodiamonds (DNDs), the smallest class of diamond nanocrystals, has become a research focal point. This approach holds potential for the noninvasive introduction of diamond sensors into living cell organelles, enabling sensing of local structural and temperature changes with minimal disturbance. Following the successful generation of silicon- and germanium-vacancy centers in DNDs, the generation of tin-vacancy (SnV) centers was investigated. Similar to other group-IV color centers, the SnV centers exhibit strong photoluminescence. In addition, the SnV center offers a long spin coherence time compared with those of silicon- and germanium-vacancy centers. However, the strain induced by large Sn atoms poses substantial challenges for generating SnV centers in ultrasmall nanodiamonds. In this study, Sn-doped DNDs with a mean particle size of ~ 5 nm were subjected to a 3 days boiling acid treatment, which led to sharp zero-phonon lines of SnV centers at ~ 620 nm in the photoluminescence spectra. Photon autocorrelation measurements further revealed the presence of single SnV centers in these DNDs.